Persuasiveness of Celebrity Endorsed Advertising and a New Model for Celebrity Endorser Selection - Fang, Lin; Jiang, Yanqing (Journal of Asian Business Strategy, 2015)
With the rapid paces of product diversification and competition intensification in most commodity markets, there have been more and more ways for sellers to introduce new products and promote existing products, and for buyers to get to know those products. Using celebrities as product endorsers has become one such important way. Therefore, the selection of the most suitable celebrity endorsers becomes an important issue that businesses and advertising agencies have to face. In this paper, based on our review of a handful of representative celebrity selection models, we analyze why and how celebrity endorsers would exert persuasion towards target consumers. We also identify key factors that would influence endorsers’ persuasiveness in advertising. More importantly, we introduce our new “Ideal Match-Up Model” for celebrity endorser selection, and apply a suppositional example to illustrate how this model can work in various cases of practical use.